In Vitro Evaluation of Effect of Different Essential Oils in Management of Post-Harvest Fruit Rot of Banana (Musa Paradisiaca) Caused by Colletotrichum spp - Gairhe, Pramod; Bhandari, Sandesh; Sitaula, Hom Prasad; Karki, Beautina; Manandhar, Hira Kaji (International Journal of Applied Sciences and Biotechnology, 2021)
A study was conducted to evaluate the in vitro efficacy of different essential oils in the management of post-harvest fruit rot of banana. It was carried out in completely randomized design (CRD) with three replications and six treatments at Nepal Plant Diseases and Agro Associates (NPDA). The each of six treatments: cinnamon oil (Cinnamomum verum), mustard oil (Brassica oleracea), castor oil (Ricinus communis), neem oil (Azadirachta indica), coconut oil (Cocos nucifera) and control were used at concentrations 200ppm, 500ppm and 1000ppm respectively. The radial growth of mycelium (mm) and percent growth inhibition (%) of Colletotrichum spp. was recorded. The decrease in the radial growth and increase in the percent growth inhibition was found in all the treatments except control as their concentration was increased, in which the lowest radial growth and the highest percent growth inhibition was found at 1000 ppm concentration. At 1000 ppm concentration, cinnamon oil shows the lowest radial growth and the highest percent growth inhibition (1.67mm and 98.15%) followed by mustard oil (54.00mm and 40.00%), neem oil (55.17mm and 38.70%), castor oil (55.83mm and 37.96%), coconut oil (61.17mm and 32.04%) and control (90mm and 0.00%) respectively.Thus, cinnamon oil is considered as a good essential oil in regards to a management of post-harvest disease of banana. Int. J. Appl. Sci. Biotechnol. Vol 9(3): 187-192.